MATERNAL AND FETAL TOXICITY-INDUCED BY NICKEL OXIDE NANOPARTICLES ADMINISTRATION IN ALBINO RATS DURING GESTATION - HAMDI, HAMIDA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Despite the widespread of nickel oxide nanoparticles (NiO NPs) and their benefits in all fields, they have many negative effects on human life, especially expectant mothers and their fetus. The purpose of this study was to investigate the possible maternal and developmental toxicity-induced by NiO NPs administration during gestation. Methods: Three groups of pregnant rats were administered orally during days 5–19 of gestation, the pregnant rats were haphazardly designed into three groups (six rat/group), as follows: Control group and NiO NPs administered groups, low (4 mg/kg), and high (8 mg/kg) doses. Results: NiO NPs administration resulted in severe maternal and developmental toxicity which included reduction in uterine weight, mother weight gain, the average weight of placenta, the number corpora lutea, implantation sites, and the number of live fetuses. Furthermore, high pre/ postimplantation, fetal growth retardation, and morphological and skeletal anomalies, an elevation in liver and brain DNA damage in both mother and fetus, and histopathological alterations in different tissues (placenta, liver, kidney, and brain) of pregnant rats and fetuses. Lipid peroxidation showed a significant elevation in maternal, fetal liver, and brain tissues of NiO NPs ‐administered rats. Furthermore, glutathione content and catalase activity were decreased in both tissues of NiO NPs‐administered rats. Conclusion: Finally, the detrimental impacts of NiO NPs in dams and fetuses probably through its potential generation of reactive oxygen species.